Early procalcitonin dynamics in critically ill patients with sepsis in a tertiary ICU - Mat Nor, Mohd Basri; Md Ralib, Azrina; Abdullah, Nor Zamzila; Mohamed, Abdul Hadi (2013)
Introduction: In critically-ill patients, procalcitonin has been studied as an assessment of appropriateness of therapy, evaluation of sepsis severity and tailoring antibiotic prescription. Objectives: We evaluated serum PCT levels relative to patient characteristics, infectious status, and presence of septic shock, SOFA score and mortality. The second objective is to define if early PCT dynamics within 48 hours may predict prognosis of critically-ill patients with sepsis. Methods: A prospective observational study was conducted in heterogeneous adult ICU at a tertiary hospital. A total of 95 consenting ICU patients aged above 18 years fulfilling criteria for SIRS were enrolled. Daily serum concentrations of PCT, C-reactive protein (CRP) and white cell count (WCC) were measured over a period of three days. Results: The median PCT concentrations between the medical vs. surgical categories and culture positive vs. culture negative sepsis were not significantly different. There was a stronger correlation between PCT and SOFA score in sepsis group, r=0.62 compared to SIRS, r=0.57. Among sepsis cohort, delta PCT at 48 hours were significantly difference between survivors and non-survivors (p=0.04). Death occurred in 59.3% of patients where PCT was decreased by < 30% on day three and in 22.2% of those where PCT was decreased > 30% (p=0.003). In patients with septic shock, PCT was persistently higher than sepsis and SIRS group without shock throughout the study period. Conclusion: PCT dynamics during the first 3 days of ICU admission with sepsis were similar in medical and surgical patients and in those with culture positive and culture negative sepsis. Early changes of PCT within 48 hours may give early information on prognosis.